Digital Innovation in E-Commerce Education Towards Industry 5.0: Improving Student Competencies and Insights A Systematic Literature Review - Darman, Andrianus; Suprianto, Agus; Wati, Andi Prasetyo; Murwani, Fulgentius Danardana; Wardana, Ludi Wishnu (PT. EQUATOR SINAR AKADEMIA, 2024)
The systematic literature review article on digital innovation in e-commerce education towards Industry 5.0 has the aim of; (1) digital innovation can be applied in the context of e-commerce education in Industry 5.0, (2) Students are prepared from university to face changes in the e-commerce business environment in Industry 5.0, and (3) students' competencies and insights need to be expanded from university. to new developments in the e-commerce business. Increasing e-commerce competence and insight for students is very important for increasing economic income and being able to compete in the global market. The method for writing a systematic literature review (SLR) article is the library research method sourced from Scopus, Emerald Publishing, and Sage Journal databases. The results of this literature review research are increasing student competence and insight in the e-commerce business through the ability to read customer behavior, the ability to minimize risks, the ability to read opportunities, and digital communication skills. These four components are students' strengths in running an e-commerce business in a dynamic digital innovation environment.